Current evidence on traditional Chinese exercise for cancers : a systematic review of randomized controlled trials - Song, Yang (2021)
Traditional Chinese exercise (TCE) has gradually become one of the widespread complementary therapies for treatment and recovery of cancers. However, evidence based on the systematic evaluation of its efficacy is lacking, and there appears to be no conclusion regarding the setting of TCE interventions. The purpose of this systematic review is to summarize the current randomized controlled trials (RCTs) that outline the effects of TCE on cancer patients. Relevant studies were searched by GOOGLE SCHOLAR, SCIENCEDIRECT, and WEB OF SCIENCE using “traditional Chinese exercise” and “cancer.” Only RCTs published in peer-reviewed English journals were included. A total of 27 studies covering 1616 cancer patients satisfied the eligibility criteria for this review. Despite the methodological limitation and relatively high risk of bias possessed by some included studies, positive evidence was still detected on the effects of TCE on these cancer-related health outcomes in physical, psychological, and physiological parameters. The 60-min or 90-min course of TCE intervention for two to three times per week for 10 to 12 weeks was found to be the most common setting in these studies and has effectively benefited cancer patients. These findings add scientific support to encourage cancer patients to practice TCE during or after conventional medical treatment. Nevertheless, future well-designed RCTs with improved methodology and larger sample size on this field are much warranted for further verification.